PvT-HADDOC: A multi-axial strain analyzer and cure monitoring device for thermoset composites characterization during manufacturing. (October 2017) - Péron, Mael; Cardinaud, Romain; Lefèvre, Nicolas; Aubril, Julien; Sobotka, Vincent; Boyard, Nicolas; Le Corre, Steven
Abstract: Process-induced strains have an important role on the development of residual stresses and final dimensions of composite parts. It is of utmost importance to characterize them in order to optimize the process conditions. This paper is devoted to the presentation of a new device, which can measure the curing strains of thermosetting composite materials under process representative conditions (temperature and pressure up to 200 °C and 1.0 MPa, respectively). The sample strains are recorded along two directions (through-thickness and in-plane), and the degree of cure is estimated in the same time. The device has been thoroughly validated thanks to several tests, demonstrating its accuracy. Two specific materials were tested, i.e. a glass-vinylester SMC and a UD carbon-epoxy composite. The measured coefficients of thermal expansion and of chemical shrinkage are in excellent agreement with both theoretical and experimental values available in the literature.